Nytt från Arresten - Bergman, Torsten; Pro Gardberg Center (Pro Gardberg Center, 2007)
Yhteenveto.
Keywords: kotiseutuarkistot; kotiseututyö; arkistot; paikallishistoriat (historiikit); historia; hembygdsarkiv; hembygdsarbete; arkiv; lokalhistoriker; Karjaa; Karis